TRANSPORT TARIFF POLICY IN RUSSIA IN THE PERIOD OF MONETARY FORMS OF VALUE FOUNDATION - T. Gainochenko (Publishing House of the State University of Management, 2016)
The article examines the origins and development of the railways tariff policy in Russia in the period of transformation toward monetary form of value, highlighted the stages of its evolution, and analyzes the most interesting ideas, concepts and approaches set forth by Russian government officials, academics and business community in the context of national transportation system development.